DETERMINATION OF PARAMETERS OF TECHNOGENIC AND NATURAL SOILS BY COMPLEX OF RADIOISOTOPE LOGGING (BY THE EXAMPLE OF ASH DUMPS OF TRYPILLIAN HEAT POWER STATION) - Bondarenko, M.; Кulyk, V.; Кеtov, A.; Deineko, S.; Ivaschenko, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The expanded set of engineering geology and petrophysical parameters of soils in territory of ash dump of Trypillian heat power station on the basis of an object-adaptive procedure of radioisotope loggings methods (RL) complexation is determined. It is shown high informativity of complex of RL-methods at technogenic soils investigations – ash dumps of heat power station.